Crystal plasticity assessment of inclusion- and matrix-driven competing failure modes in a nickel-base superalloy. (15th September 2019) - Bandyopadhyay, Ritwik; Sangid, Michael D.
Abstract: Two competing failure modes, namely inclusion- and matrix-driven failures, are studied in a Ni-base superalloy, RR1000, subjected to fatigue loading using crystal plasticity finite element (CPFE) simulations. Each individual factor related to the inclusion, which may contribute to crack initiation, is isolated and systematically investigated. Specifically, the role of the inclusion stiffness, loading regime, loading direction, a debonded region in the inclusion-matrix interface, microstructural variability around the inclusion, inclusion size, dissimilar coefficient of thermal expansion (CTE), temperature, residual stress, and distance of the inclusion from the free surface are studied in the emergence of two failure modes. The CPFE analysis indicates that the emergence of a failure mode is an outcome of the complex interaction between aforementioned factors. We observe the possibility of a higher probability of failure due to inclusions with increasing temperature, if the CTE of the inclusion is higher than the matrix, and vice versa. We do not find any overall correlation between the inclusion size and its propensity for damage, based on an inclusion that is of the order of the mean grain size. Finally, the CPFE simulations indicate that the surface inclusions are more damaging than the interior inclusions for similar surrounding microstructures. Graphical abstract: Image 1